Multiomics integration for the function of bacterial outer membrane vesicles in the larval settlement of marine sponges - Zhang, Beibei; Jia, Chenzheng; Li, Mingyu; Wang, Kai; Chen, Jun; Zhao, Jing (Frontiers in Microbiology, 2024)
Bacterial outer membrane vesicles (OMVs) containing a variety of chemical compounds have important roles in maintaining symbiotic relationships in a changing ocean, but little is known about their function, particularly in sponge larval development. During the growth of sponge Tedania sp., OMVs from Bacteroidetes species significantly promoted larval settlement, and Tenacibaculum mesophilum SP-7-OMVs were selected as a representative strain for further investigation. According to OMVs metabolomics, larval settlement may be connected to organic acids and derivatives. The multiomics analysis of the T. mesophilum genome, SP-7-OMVs metabolome, and larval transcriptome revealed 47 shared KEGG pathways. Among a number of candidate metabolites, arginine was chosen for its greater ability to increase settlement rate and its role as the principle substrate for nitric oxide (NO) synthesis of sponge larvae. In summary, these results demonstrated that sponge-associated bacteria might utilize OMVs and their cargo to support host development and make up for host metabolic pathway deficiencies. This study enhanced our fundamental knowledge of OMVs in interactions between metazoan hosts and microorganisms that was crucial in the coevolution of marine ecosystems and the complex marine environment.